Parents' Views on the Implementation of TPQ in Increasing Students' Religious Understanding - Juandi pasaribu; Martin Kustati; Rezki Amelia (Departement of PAI, Universitas Majalengka, 2023)
The rapid development of technology has made parents of students at the Muhajirin Mosque Al-Qur'an Education Park (TPQ/TQA) in Air Dingin Lubuk Minturun Padang pay less attention to their children's religious education. TPQ/TQA institutions have a very important role for students to recognize the Qur'an and shape students' understanding of religion. This study aims to describe parents' perceptions of the implementation of TPQ/TQA in improving students' religious understanding. This type of research is qualitative descriptive, the data collection techniques used are observation, interviews, documentation and data analysis. The results showed that the Parents' Views on the Implementation of TPQ / TQA in Improving Religious Understanding are good, it is evidenced by the students' easier understanding of learning and changing behavior so that they become better students, and also motivating students to study harder, besides that, through the implementation of TPQ / TQA students are taught to help each other. This research also reveals that parents are very careful about TPQ/TQA as a place to learn to read and write the Qur'an for their children.